Teaching a tolerance for ambiguity as a response to crisis learning contexts - Long, Jennifer (My University, 2021)
Using insights from the changes made to a workshop developed before, but occurring after the pandemic, I describe the usefulness of design thinking activities and approaches to education in the post-COVID teaching era. I argue that design thinking techniques help build awareness around tolerance for ambiguity as an opportunity to inspire creative teaching solutions. This transferable skill is important for our students as soon-to-be graduates, and for faculty looking to build resilience in this uncertain time. Using Boyer’s framework for scholarship, I explore opportunities to connect the teaching and learning goals of students and faculty.
Keywords: tolerance for ambiguity; design thinking; COVID-19; resilience; Boyer’s definition of scholarship